The Image Of Bukhara In “The Story Of The Indian Traveler” - Eshmurzayeva Barno (Genius Journals, 2026)
This scholarly and analytical article comparatively examines Abdurauf Fitrat’s work “The Indian Traveler” (or a critical text inspired by this work) from the perspective of Western Enlightenment ideas and the Jadid movement of Turkestan. The work provides a critical analysis of the socio-political crisis in the Bukhara Emirate, particularly focusing on the condition of the three social strata of society — the Ulama, the Umara, and the Fuqara. The article reveals that Fitrat sought the causes of the decline of the Islamic world in Bukhara’s scientific stagnation and corruption in governance. “The Indian Traveler” is evaluated not merely as a geographical description, but as a socio-political manifesto that promotes Jadid ideas such as humanism, social justice, education, and critical thinking, calling the people to awaken from ignorance. The analysis emphasizes the significance of Fitrat’s work both in its own period and in subsequent educational processes.
Keywords: Abdurauf Fitrat; Jadidism; ulama; umara